Enhanced Photocatalytic Degradation of Rhodamine B Using C/Fe Co-Doped Titanium Dioxide Coated on Activated Carbon - Thuy Le Thi Thanh; Lan Nguyen Thi; Trinh Tran Dinh; Noi Nguyen Van (My University, 2019)
Enhanced Photocatalytic Degradation of Rhodamine B Using C/Fe Co-Doped Titanium Dioxide Coated on Activated Carbon
Keywords: C/Fe Co-Doped